Women Participation in School Governance in Lalitpur, Nepal: A Participatory Development Practice - Adhikari, Rishi; Adhikari, Devendra (Nepalese Journal of Development and Rural Studies, 2021)
Participation is an important dimension of good governance. In Nepal, there seem positive changes in women’s participation in School Management Committees (SMC), Parent Teachers Association (PTA), and school administration but the participation of women has become a far-reaching goalin public school governance. This article is about exploring how women’s participation could contribute to promoting good governance practices in community schools. Authors have applied an interpretative inquiry and participation and feminist standpoint theories to make out the meaning in this study which was carried in two public schools in Lalitpur, Nepal. The finding reveals that his meaningful representation of women in school governance is likely to minimize the governance challenges such as absenteeism, low parents’ participation, poor resource mobilization, transparency, and accountability.These positive transformations contribute to the community development process. However, enabling environment for women is needed to ensure their meaningful representation in school governance structures. This study is beneficial to educationists, planners, and development workers in Nepal.